FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN ISPA PADA BALITA DI PUSKESMAS PASARKEMIS, KABUPATEN TANGERANG - Faridha Aulia; Lukman Fauzi (Jurnal Kesehatan Masyarakat, 2023)
ARI incidence at Pasar Kemis Public Health Center is the highest infectious disease case in last 2 years. The prevalence of ARI at Pasar Kemis Public Health Center was 9.2% for all age groups and 10.9% for children under fives, while in 2020 it was 8.9% for all age groups and 5.3% for children under fives. This shows that ARI cases in 2020 decreased compared to 2019. The purpose of this study was to determine the factors associated with ARI incidence in children under five. This type of research is analytic observational with a case-control design by taking primary data in working area of Pasar Kemis Public Health Center. The dependent variables in this study are nutritional status, exclusive breastfeeding, immunization status, family members smoking behavior, use of mosquito coils, garbage burning behavior, ventilation area, residential density and economic status and the independent variable was ARI incidence. The sample size used was 33 case samples and 66 control samples with data inclusion and exclusion techniques. The instruments are questionnaires, roll meters, microtoise, and scales. Data were analyzed by univariate, bivariate, and multivariable with Chi Square technique and processed using SPSS. Result shows that birth weight (p value=0.00; OR=8.62; 95% CI=1.68-44.25) and house ventilation (p value=0.02; OR=3.63; 95% CI=1.13-11.61) correlated with ARI incidence in children under five. Factors that most correlated is birth weight (p value=0.02; OR adj=5.55; 95% CI=1.23-24.92). Suggestion in this research is to pay attention to pregnant women’s nutrition so that they don’t give birth with low birth weight and pay attention housing health.